Closed for the Season : A Mystery Story - Hahn, Mary Downing (Boston : Clarion Books, 2009)
When Logan and his family move into a run-down old house in rural Virginia, he discovers that a woman was murdered there and becomes involved with his neighbor Arthur in a dangerous investigation to try to uncover the killer.
A Junior Library Guild selection
Keywords: Homicide -- Fiction; Friendship -- Fiction; Virginia -- Fiction; Juvenile horror